STRUCTURAL PROPERTIES AND GROWTH DYNAMICS OF A UNEVEN-AGED PURE PINE FOREST STAND (GEOMATE Journal, 2025)
This study examines the growth dynamics and structure of an uneven-aged pure Scots pine (Pinus sylvestris) stand in the alpine zone at elevations between 1800 and 2200 meters in Georgia, with the forest ending at 2188 meters. The research site was centered at 2056 meters, where a one-hectare plot was selected. To avoid edge effects, we chose a denser part of the forest rather than the border, ensuring natural resource distribution. Data on tree height, diameter at breast height (DBH), and annual growth increments were collected from a randomly selected plot. Dendrochronological analysis showed younger trees (